High-Speed Wireline Links—Part II: Optimization and Performance Assessment - Hossein Shakiba; Davide Tonietto; Ali Sheikholeslami (IEEE Open Journal of the Solid-State Circuits Society)
In Part I of this article, we described the modeling of a general wireline link architecture. In this part, we provide a scheme for optimizing the link parameters and assessing its performance. The optimization process involves many parameters with constraints coming from application and implementation requirements. A brute-force approach to optimization can take a prohibitively long time and may not provide sufficient insight into the design iteration. To address this challenge, we divide the optimization process into specifying fixed parameters, calculating select parameters, and sweeping the rest. We then perform a link performance assessment to determine metrics typically used in wireline systems.